Pemanfaatan Teknologi Digital dalam Manajemen Keuangan pada Warga Perumahan Benda Baru Pamulang dengan Aplikasi My Report - Agus Salahudin; Reza Muhammad; Hanie Supandi; Jasica Asih Hati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The use of digital technology in financial management has rapidly developed, with financial management applications, fintech services, and digital banking platforms becoming increasingly popular, including in Indonesia. This study aims to identify the benefits and challenges faced by society in adopting digital technology for financial management. The results show that digital technology provides broader access to financial services, enhances financial literacy, and facilitates efficient budget and investment management. Additionally, fintech helps SMEs access financing. However, challenges such as low digital literacy, data security issues, and limited access to technology in certain areas remain significant barriers. Therefore, educational programs and financial inclusion policies are necessary to maximize the potential of digital technology in financial management. Overall, digital technology can have a positive impact on financial management in society, provided that risks are mitigated, and accessibility is improved.